1995
DOI: 10.1177/0148607195019004310
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Deposition in the Brain During Long‐Term Total Parenteral Nutrition

Abstract: It is probable that the high manganese level was elicited by manganese supplementation to total parenteral nutrition. This high manganese condition was confirmed by the measurement of whole-blood manganese level, which was associated with the abnormal high intensity lesions on T1-weighted magnetic resonance images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 5 publications
2
44
0
Order By: Relevance
“…No neurologic symptoms or complaints were recognized in the present case. An abnormally high intensity on T1-weighted MRI after total PN therapy has been reported to be reversible in most cases [10,12]; it also improved in the present case. However, once deposited in the brain, Mn is cleared extremely slowly, even if parenteral administration is stopped [16,32].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…No neurologic symptoms or complaints were recognized in the present case. An abnormally high intensity on T1-weighted MRI after total PN therapy has been reported to be reversible in most cases [10,12]; it also improved in the present case. However, once deposited in the brain, Mn is cleared extremely slowly, even if parenteral administration is stopped [16,32].…”
Section: Discussionsupporting
confidence: 66%
“…MRI abnormalities in the brains of patients with liver disease are common, and are observed most often in patients with portal-systemic shunting and neurological dysfunction [5,6]. Recently, an elevation in blood Mn levels and MRI abnormalities in the brain have also been reported in patients with long-term total parenteral nutrition (PN) with multi-trace element supplement solutions [7][8][9][10][11][12]. A recent report has suggested that even short-term total PN therapy with Mn supplement may cause Mn toxicity in patients with obstructive jaundice following an increase in blood Mn concentrations, as a result of reduced biliary flow [13].…”
Section: Introductionmentioning
confidence: 99%
“…Mn intoxication associated with TPN solutions providing ≥ 0.1 mg Mn/day is well established (Bertinet et al, 2000;Nagatomo et al, 1999;Ono et al, 1995). These patients developed elevated serum Mn levels (Takagi et al, 2002), and they exhibit symmetrical high intensity MRI lesions in the globus pallidus consistent with the preferential accumulation of Mn at this site, in association with characteristic psychiatric symptoms and clinical signs of Mn-induced parkinsonism-like syndrome.…”
Section: Parenteral Exposurementioning
confidence: 99%
“…Abnormalities on brain T1-weighted MRI and elevated blood Mn concentrations caused by PN therapy have been reported to be reversible [10, 12, 13]. A clinically important finding, however, is that normalization of the elevated blood Mn levels required at least 2 months after stopping Mn administration (fig.…”
Section: Discussionmentioning
confidence: 99%
“…MRI abnormalities in the brain in patients with liver disease are common, and are observed most often in patients with portal-systemic shunting and neurological dysfunction [3, 4]. Recently, elevation of blood Mn levels and T1-weighted MRI abnormalities in the brain, especially in the basal ganglia, were reported in patients receiving long-term PN with multi-trace-element supplement solutions exceeding 5 months [5, 6, 7, 8, 9, 10]. The possibility of abnormal Mn deposition due to short-term perioperative PN therapy in patients undergoing gastroenterological surgery has not previously been discussed.…”
Section: Introductionmentioning
confidence: 99%